الضوابط القانونية الحاكمة للإدارة في إعداد اللائـحـــة التـنـفـيــذيـــة - تركي خلف, عيسى (Journal of College of Education, 2021)
The exercise of the statutory authority of its function represents an exception from the origin stating that the legislative authority takes over the function of legislation, and the implementation of this exception requires the availability of legal, technical and practical justifications, and likewise, the exercise of this statutory function is governed by objective controls that require that the statutory authority be committed during the preparation of the regulation to come to its place or content By the law. The regulations relating to the content of the executive regulations vary according to special constitutional controls And which is imposed by the principle of subsidiarity which stipulates that the regulations must not violate the law that was issued to implement it in the event of its preparation, and general constitutional controls Which stems from the subjection of the bylaw to the principle of legislative progression which imposes on the regulatory authority the obligation not to violate all the higher rules of standing in the bylaw